Inter‐relations among negative social control, self‐efficacy, and physical activity in healthy couples. Issue 3 (8th March 2018) - Hohl, Diana Hilda; Lüscher, Janina; Keller, Jan; Heuse, Silke; Scholz, Urte; Luszczynska, Aleksandra; Knoll, Nina
Abstract : Objectives: In romantic relationships, partners can influence each other's health‐relevant behaviour by exerting negative social control (e.g., pressuring), however, with mixed success. To elucidate this phenomenon, we examined couples motivated to increase their physical activity and investigated the degree to which both partners exerted negative control on each other, their self‐efficacy, reciprocal associations among the two behaviour‐specific constructs, and their relationship with moderate‐to‐vigorous physical activity (MVPA). Design: This was a longitudinal study with three assessment periods (T0, T2, T3) spanning 7 weeks. Methods: We performed secondary analyses with data from the control condition ( N = 113 heterosexual couples) of a published randomized controlled trial. Dyadic mediator models specified either both partners' self‐efficacy as predictors and provided negative partner control to each other as mediators or vice versa. The outcomes comprised both partners' accelerometer‐assessed MVPA. Mediators and outcomes were controlled for their T0 values. Results: The first model showed that women's and men's provided negative partner control (T0) was positively related to the other partners' self‐efficacy (T2). Testing the alternative predictive direction, the second model showed that only women's self‐efficacy (T0) was associated with more provided negative partner control (T2) by men. Women and men showed less MVPA (T3) when their partners had provided them with more negative control at T2. Conclusions: As negative control provided to partners may be detrimental to their behaviour change, interventionists should advise couples to avoid it. However, active ingredients of negative control that may benefit recipients' self‐efficacy beliefs should be investigated in future work. Statement of contribution What is already known on this subject? Couples often try to change each other's health behaviour not just using supportive tactics, but also controlling ones. Negative partner control (e.g., rebuking and nagging) was found to have adverse or no effects on control recipients' health behaviour change. To understand underlying mechanisms of this relationship, reactance and negative affect of recipients have been investigated, but only rarely their self‐efficacy, a consistent individual predictor of behaviour change that is likely to share reciprocal relations with social exchange processes, including negative social control. What does this study add? Although harmful for behaviour change, negative partner control may increase control recipients' self‐efficacy. Higher self‐efficacy of one partner may also increase provided negative partner control by the other.